Comparison of Discharge Using Manning's and Strickler's Methods in the Primary Canal of Gebong Weir, West Lombok Regency - Muhamad Yamin; Agus Winardi; Wirriyanti Isnasari; Masitha Maghfirah (SainsTech Innovation Journal, 2026)
This study aims to analyze and compare the flow discharge in the primary canal of Bendung Gebong using the Manning and Stickler methods. The research was conducted to determine the differences in discharge calculation results and to identify the most suitable method for stone masonry channels. The research data were obtained through direct field measurements, including the top width, bottom width, water depth, and channel bed slope. The measured channel dimensions consisted of a top width of 10 m, bottom width of 7 m, water depth of 1.40 m, and channel bed slope of 0.001. The method used in this study was open channel hydraulic analysis by calculating hydraulic parameters such as wetted area, wetted perimeter, and hydraulic radius. Furthermore, discharge calculations were carried out using the Manning and Stickler equations. The analysis results showed that the wetted area was 11.9 m², the wetted perimeter was 11.10 m, and the hydraulic radius was 1.07 m. The discharge calculated using the Manning method was 13.10 m³/s, while the Stickler method produced 12.97 m³/s. The comparison results indicated a discharge difference of 0.13 m³/s with a percentage difference of 0.99%. The relatively small difference indicates that both methods provide nearly similar results under stone masonry channel conditions. The Manning method produced a slightly higher discharge than the Stickler method and was considered more practical for irrigation channel hydraulic analysis.